Diversity of Morphological Character and Relationship of Gelugur Acid (Garcinia atroviridis Griff. Ex T. Anders) in Asahan Regency and Batubara Regency in North Sumatra - Widia Febrianti; Eva Sartini Bayu; Revandy Iskandar M. Damanik (Jurnal Agroekoteknologi, 2018)
This research aims to identify morphological character and relation plant of acid gelugur (Garcinia atroviridis Griff. Ex T. Anders) that exist in Regency of Asahan and Regency of Batubara in North Sumatera. This research was conducted in Asahan and Batubara regency in February-April 2017 with survey method using IPGRI gelmatic descriptors guide. Sampling technique is accidental sampling. The results showed that in three regencies of Sumatera Utara there were 20 accessions of gelugur acid that identified Asahan Regency there were 9 accessions and there were 11 accessions of Batubara Regency. Result of morphological characterization for crown shape (pyramid, round, longitudinal and pattern-shaped), stem surface (slippery, coarse, very coarse), leaf (jorong, elongated, lanceolate), flower (female flowers and hermaphrodite flowers) , Evenly, longitude, longitude). The lowest dissimilarity value or the closest kinship relationship in Asahan and Batubara regency is 1,390 with 4 differences from 19 qualitative characters and the highest dissimilarity value or the furthest kinship relationship in Asahan and Batubara regency is 63,636 with 7 differences from 19 qualitative characters   Keywords : garcinia atroviridis, identification, kinship relationship, morphologycal characteristics